Pengaruh Budaya Organisasi Islam, Kepemimpinan Inklusif Dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Beban Kerja Sebagai Variabel Moderasi : Studi Pada PT Buya Barokah Kudus - Fatonah, Umi; Setiawan, Ari (Universitas Muhammadiyah Sumatera Utara, 2025)
This study aims to identify the influence of Islamic organizational culture, inclusive leadership and work environment on employee performance with workload as a moderating variable. The population of this study was 150 employees of PT. Buya Barokah Kudus Bottled Drinking Water Division with a sample of 109 people. Data were obtained through a questionnaire with an interval scale of 1-10 and analyzed using SPSS Version 27. The results showed that Islamic organizational culture and work environment had a positive and significant effect on employee performance, while inclusive leadership had a negative and insignificant effect on employee performance. Workload was not able to moderate the influence of the three variables on employee performance. The contribution of the three variables to employee performance moderated by workload was 43.7% while the remaining 56.3% was influenced by other variables not explained in this research model.